TEKNIK PENULISAN NASKAH FEATURE “KOLAM SUSU” DENGAN STRUKTUR ORGANIK DAN POLA PARALEL - Tsurayya Zahirah; Halimatus Sa’diyah; Fadeyanto Prabowo (Jurnal Ilmu Komunikasi AKRAB, 2020)
This feature tells about the life of people who have a profession as cow milker in Boyolali, from a life of always working hard to provide nutritional intake for the best processed cows in the hope that cows can provide quality milk which will benefit the milkman. However, sometimes the struggle of the cow farmer is insignificant when compared to the wages and results that have been earned. With an increasingly modern development, making this processed milk into quality products and processed by the Boyolali community itself. Therefore, some people there make processed in solid form such as milk snacks, milk candy, milk chips and many others made from pure milk. So that not only liquid milk can be used as souvenirs but other solid products as well. The writing used in the production of this feature uses organic structures and parallel patterns. Here, the author will focus more on the information to be conveyed, in this feature program information will be conveyed clearly through visual images and audio in the form of voice over which will convey in detail through language selection, sentence arrangement in each paragraph which is very informative. This work is packaged in a duration of 24 minutes including a bumper and credit title. This “Milk Pool” feature has a message of the value of life that inspires and provides information about the city of Boyolali.